2020
DOI: 10.1038/s41598-020-75754-7
|View full text |Cite
|
Sign up to set email alerts
|

Masking terminal neo-epitopes of linear peptides through glycosylation favours immune responses towards core epitopes producing parental protein bound antibodies

Abstract: Glycosylation of hydrophobic peptides at one terminus effectively increases their water-solubility, and conjugation through the opposing end to a carrier protein, renders them more immunogenic. Moreover, the glycosylation minimizes antibody responses to potentially deleterious, non-productive terminal neo-epitope regions of the peptides, and consequently shifts peptide immunogenicity towards the core amino acid residues. As proof of concept, glycopeptide-protein conjugates related to influenza hemagglutinin (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…However, the waning of responses over time in our rabbit study could indicate that some optimization of the RHDV conjugates may be required. It would be interesting to determine if altered peptide loading per CRM 197 molecule or the masking of terminal neo-epitopes on the linear peptides would enhance longevity of responses [ 43 ]. An altered peptide loading profile on the carrier could potentially reduce the induction of anti-carrier antibodies, which have been previously shown to reduce the levels of responses following subsequent vaccinations with conjugate antigens using the same carrier [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the waning of responses over time in our rabbit study could indicate that some optimization of the RHDV conjugates may be required. It would be interesting to determine if altered peptide loading per CRM 197 molecule or the masking of terminal neo-epitopes on the linear peptides would enhance longevity of responses [ 43 ]. An altered peptide loading profile on the carrier could potentially reduce the induction of anti-carrier antibodies, which have been previously shown to reduce the levels of responses following subsequent vaccinations with conjugate antigens using the same carrier [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“… 55 Applications of this concept in recent reports demonstrated that masking the terminal amino acids of peptide antigens with weakly immunogenic glycosylation can shift the immune response toward central residues, providing a path toward the generation of effective domain-specific mAbs using peptide fragments. 56 , 57 …”
Section: Domain-specific Targeting For Elisa Antibodies To Prevent Interferencementioning
confidence: 99%
“…Notably, synthetic peptides are increasingly replacing biological molecules in diagnostic tests ( 14 , 15 ). Moreover, unequivocally characterized peptide antigens can display enhanced specificity for recognition, thereby eliminating or minimizing potential cross-reactivity between structurally homologous protein epitopes ( 16 18 ). Individual antigenic epitope mapping of native proteins provides useful information that can assist in the design of peptide-based diagnostic tests and peptide libraries for monitoring specific cellular immunity in patients ( 19 21 ).…”
Section: Introductionmentioning
confidence: 99%